STRATEGI KOMUNIKASI PEMASARAN PROGRAM INTERAKTIF DI RRI PRO 2 FM JAKARTA - Azhar Hutomo (Jurnal Komunikasi, 2017)
The result of empirical study, that RRI Pro 2 FM Jakarta has conducted marketing communication of it’s interative programme in the frame of attracting the audience toward the advertiser through two strategies both push strategy and pull strategy such as advertisement, promotion, public relation and publicity, personel selling and direct selling. However, the result of its advertisement has been unoptimum as the private radio in Jakarta worked. The results of analysis of qualitative approach by SOSTAC method (Situation, Objective, Strategy, Tactics, Action, Control) is gotten the result that marketing communication of interative programme through advertisement, promotion, public relation and publicity, personel selling and direct selling at RRI Pro 2 FM Jakarta has been not conducted maximally due to the limited number of marketing, so the gained commercial advertisement has not met an existing quota. This is caused by having not been supported a planning, implementing and evaluation effectively, sistemically, integratedly and comprehensively as the impact of having not been fully encouraged by quality and quantity of organizer’s human resources of RRI Pro 2 FM Jakarta sufficiently, especially Marketing Human Resources those are involved durctly in marketing communication of interative programme.Keyword: Strategy Of Marketing Communication, Interative Programme, Radio